Sharpening Early Digital Literacy Skills as a Long-Term Investment for Young Children - Nur Amalina (AGENDA: Jurnal Analisis Gender dan Agama, 2023)
AbstractIn today's rapidly advancing digital era, the ability to master technology has become crucial for everyone. Nearly all activities can be carried out using technology, especially digital technology that is accessible by anyone, anytime, and anywhere, from adults to young children. However, it's important to note that young children, who are in a crucial stage of growth and development, are highly susceptible to environmental influences, including digital technology which is now easily accessible to them, often with parental permission to use gadgets. Therefore, this is a significant concern because in the age range of 0-6 years, a child's brain development progresses rapidly, reaching up to 80%, allowing their brains to easily absorb various information, both positive and negative.This period is often referred to as the "golden age," which requires close supervision from adults regarding the use of digital technology by young children. Strict supervision is necessary because digital technology can grant unrestricted access to young children, including access to negative content such as pornography and violent games, which can adversely impact their morals and development. Conversely, with proper guidance and supervision, the use of digital technology can offer numerous benefits to young children, such as enhancing their creativity and insights, as well as helping them explore talents and interests in the digital realm.  Therefore, the author is interested in identifying and describing the digital literacy skills of young children as a long-term investment